Cost and Benefit Analysis of Surgeon-performed Point-of-Care Ultrasound (SP-POCUS) supporting decision making in a General Surgery Department - Pezzotta, Giorgia; Masiero, Giuliano; Malagnino, Alessia; Bozzo, Samantha; Brescacin, Alessandra; Carrara, Giulia; Zago, Mauro (Mecosan - Management ed Economia Sanitaria - Open Access, 2025)
Background: There still is reluctance among surgeons when it comes to using bedside US in their daily clinical practice, except for very specific fields. Generally, the decision-making process relies on imaging techniques (e.g. CT, MRI). This may lead to a latency of execution, and consequently to a delay in decision making. Objectives: The purpose of this study is to assess the economic impact of systematic and routine use of surgeon- performed point-of-care US (SP-POCUS) in the everyday activities of a surgical department, both for urgent and elective cases. Methods: We conducted a cost-benefit analysis comparing the incremental costs and savings of diagnostic strategies based on alternative procedures to bedside US. The dataset refers to 478 SP-POCUS performed at the General Surgery Department of Policlinico San Pietro (Bergamo, Italy) between January 2018 and February 2020. The alternatives to SP-POCUS were computed tomography (CT), X-ray (RX), magnetic resonance imaging (MRI), and US performed by the Radiologist. Per-exam costs, including personnel time expenditure, were calculated. Results: The economic evaluation revealed that the use of SP-POCUS allowed the hospital to generate €355 net savings per patient, mainly from avoided hospitalizations, fewer hospital days and hours of operating room. Extrapolating these results to a wider scenario, in a similar setting they could have represented a potential annual savings of more than €1.1 million for the Regional healthcare system in Lombardy, and more than €5.7 millions for the whole NHS in Italy. Conclusions: We provided evidence that SP-POCUS may generate important costs savings for health care providers, as it represents the most cost-effective initial diagnostic procedure compared to standard alternatives. The wide applicability of SP-POCUS could be obtained at rather negligible costs for investment in staff training.